2015
DOI: 10.4161/15384101.2014.994966
|View full text |Cite|
|
Sign up to set email alerts
|

Receptor tyrosine kinase ERBB4 mediates acquired resistance to ERBB2 inhibitors in breast cancer cells

Abstract: Approximately 25% of breast cancers overexpress and depend on the receptor tyrosine kinase ERBB2, one of 4 ERBB family members. Targeted therapies directed against ERBB2 have been developed and used clinically, but many patients continue to develop resistance to such therapies. Although much effort has been focused on elucidating the mechanisms of acquired resistance to ERBB2-targeted therapies, the involvement of ERBB4 remains elusive and controversial. We demonstrate that genetic ablation of ERBB4, but not E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
72
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(76 citation statements)
references
References 35 publications
2
72
2
Order By: Relevance
“…45 As a most frequently hyperactivated signaling in plenty of malignancies, AKT pathway mediates cell survival and chemoresistance. 11 Full activation of AKT requires phosphoinositidedependent kinase 1 (PDK1) and mammalian target of rapamycin complex 2 (mTORC2) mediated phosphorylation at both Thr308 and Ser473.…”
Section: Discussionmentioning
confidence: 99%
“…45 As a most frequently hyperactivated signaling in plenty of malignancies, AKT pathway mediates cell survival and chemoresistance. 11 Full activation of AKT requires phosphoinositidedependent kinase 1 (PDK1) and mammalian target of rapamycin complex 2 (mTORC2) mediated phosphorylation at both Thr308 and Ser473.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34]38 More recently, ERBB4 has been implicated in mediating acquired resistance to ERBB2 inhibitors and in protecting epidermal growth factor receptor from degradation in breast cancer cells. 39,40 Conversely, COL29A1 encodes for the collagen VI a chain COL6A5, an extracellular matrix protein with critical roles in maintaining muscle and skin integrity. 41 In addition to structural functions, evidence suggests that collagen VI has growthstimulatory and prosurvival effects.…”
Section: Discussionmentioning
confidence: 99%
“…There are potentially oncogenic ERBB4 mutations in non-small cell lung cancer (9), and it has been reported that HER4 is overexpressed in human colon cancer and enhances cellular transformation (10). In addition, HER4 promotes breast cancer cell proliferation, mediates acquired resistance to ERBB2 inhibitors and may serve as a prognostic marker in patients with breast cancer (11)(12)(13)(14). However, the role of HER4 in CRC remains to be fully elucidated.…”
Section: Introductionmentioning
confidence: 99%